A Social Partnership Model to promote Educators’ Development in Mauritius through Formal and Informal Capacity-building Initiatives - Santally, Mohammad Issack; Cooshna-Naik, Dorothy; Conruyt, Noel; Koa Wing, Caroline (Journal of Learning for Development, 2015)
The organization Helping Our People has been setup in 2011 by a team of education professionals working at the Virtual Centre for Innovative Technologies (VCILT) at the University of Mauritius. In 2009, the VCILT embarked on the SIDECAP project, funded by the EU-ACP in a consortium regrouping the Open University of the UK, the University of the West Indies, the University of the South Pacific and the University of the Highlands and Islands. The work of the VCILT in the context of the SIDECAP project was essentially focused on the repurposing of Open Educational Resources to fit in the local Mauritian Context. At the same time, the VCILT received an internal grant to work on the development of interactive learning materials using the integration of text-to-speech technology in instructionally designed PowerPoint presentations. In this paper we report how the research activities of the two projects led to a series of development and applications in the real-world context for the continuous professional development of educators, the establishment of a social entity, an NGO called Helping Our People, a partnership with Microsoft Indian Ocean and French Pacific under the Partners in Learning Program and the Youth Empowerment Program to alleviate the suffering of those living in vulnerable conditions in the country.